Seasonal variation in frog predation by black lion tamarins (Leontopithecus chrysopygus, Primates). Issue 5 (16th February 2022) - Garbino, Guilherme S. T.; Rezende, Gabriela Cabral; Antônio, Daphne Chiara; Bufalo, Felipe; Amaral, Rodrigo Gonçalves; e Silva, Anne-Sophie de Almeida; Kaisin, Olivier; Culot, Laurence
ABSTRACT: Although lion tamarins ( Leontopithecus spp.) are known to prey upon frogs, no study has attempted to document the frequency and seasonal patterns of such events. In this study, we compiled data on frog predation by black lion tamarins, Leontopithecus chrysopygus, in south-eastern Brazil between 2014 and 2020. We investigated the effects of seasonality on predation rate and described the behaviour of the lion tamarins. In 1972 observation hours, we recorded 49 frog predation events. Predation was more intense in the beginning (April and May) and the end (August and September) of the dry season, suggesting seasonal variation. The observed pattern may be related to a combination of increased fruit availability in the rainy season and decreased frog activity in the height of the dry season. Compared to Saguinus mystax, the only other tamarin species for which there is available data, predation rate of anurans by black lion tamarins is five times higher. We suggest that frogs are an important item in the diet of black lion tamarins and reinforce the idea that vertebrate predation in some primates is seasonal.